Pengaruh Kompetensi Karyawan Terhadap Kinerja Pada Badan Perencanaan Pembangunan Daerah Kabupaten Ciamis (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This research is motivated by the results of preliminary observations that there are still jobs that do not match the specified time, The ability to communicate and master information globally to be able to adapt to environmental changes is still relatively low, The inability of each employee to implement full accountability (personal accountability) in accordance with their field of duty and function, Weak acceleration of completion of work tasks that can result in time delays, The weak ability to compile activity agendas that prioritize the needs of supporting work for autonomous regional apparatuses that are best practice, The inability to create a collaborative network (net working) with related autonomous apparatus agencies/agencies in compiling work agendas to support the smooth running of the tasks of the Regent of Ciamis. The method used is a quantitative descriptive research method. The population in this study was 49 people. The sampling technique used the total sample technique, thus the sample in this study was 49 people. The data collection technique used a questionnaire. The results of the study were as follows: The competence of employees of the Ciamis Regency Regional Development Planning Agency is included in the good category. This shows that employees of the Ciamis Regency Regional Development Planning Agency have good competence in terms of Behavioral Tools, Image Attributes, and Personal Characteristics. The performance of employees of the Ciamis Regency Regional Development Planning Agency is included in the good category. This shows that employees of the Ciamis Regency Regional Development Planning Agency have good employee performance in terms of quantity of work, quality of work, job knowledge, creativeness, cooperation, dependability, initiative, personal qualities. Employee competence has a positive effect on the performance of employees of the Ciamis Regency Regional Development Planning Agency. This means that if employees have high competence, then employee performance will be even higher. Because the provision for achieving performance is the existence of competence.